Fragmented Ijtihâd and Fatwa Governance: A Progressive Ijtihâd Analysis of the Indonesian Council of Ulama (MUI) - Nano Wahyudi; Mhd Syahnan; Ardiansyah Ardiansyah (Madania: Jurnal Kajian Keislaman, 2025)
This article examines the configuration of tajazzu’ al-ijtihâd (fragmented or partial ijtihâd) in the fatwa-making process of the Indonesian Council of Ulama (Majelis Ulama Indonesia/MUI) and evaluates it through the theoretical lens of Progressive Ijtihâd. In the context of contemporary socio-religious complexities, Islamic legal reasoning can no longer rely solely on the capacity of individual jurists; rather, it requires specialization, multidisciplinary collaboration, and adaptive interpretive methodologies. This study employs a normative-comparative approach by analyzing MUI’s Fatwa Determination Guidelines, thematic fatwas, classical theories of ijtihad, and the epistemic framework of Progressive Ijtihâd. The findings reveal that MUI’s institutional structure has, in principle, adopted a model of tajazzu’ al-ijtihâd through commission-based specialization, thematic task allocation, and the inclusion of cross-disciplinary experts. However, epistemically, MUI’s fatwa practices remain dominated by textual-normative tendencies, resulting in limited integration of empirical data, social analysis, and a comprehensive maqȃṣid-based assessment. Consequently, certain fatwas lack full responsiveness to social change and the practical needs of modern Muslim communities. This article concludes that realizing a truly progressive form of ijtihad requires MUI to strengthen methodological consistency, increase the participation of non-fiqh experts, and adopt a problem-solving approach aligned with the objectives of maqâṣid al-syarî‘ah. These findings contribute to contemporary Islamic legal theory by elucidating the challenges and relevance of institutional ijtihâd in modern Muslim societies. Artikel ini menganalisis konfigurasi tajazzu’ al-ijtihâd (ijtihad terfragmentasi) dalam proses penetapan fatwa Majelis Ulama Indonesia (MUI) serta mengevaluasinya melalui perspektif Ijtihad Progresif. Di tengah kompleksitas sosial-keagamaan kontemporer, mekanisme ijtihad tidak lagi dapat ditopang oleh kapasitas individual, tetapi memerlukan spesialisasi, kolaborasi multi-disipliner, dan metodologi interpretatif yang adaptif. Penelitian ini menggunakan pendekatan normatif-komparatif dengan menelaah Pedoman Penetapan Fatwa MUI, fatwa-fatwa tematik, teori ijtihad klasik, dan konstruksi epistemik Ijtihad Progresif. Hasil penelitian menunjukkan bahwa struktur kelembagaan MUI pada dasarnya telah mengadopsi bentuk tajazzu’ al-ijtihâd melalui pembagian komisi, penugasan tematik, dan keterlibatan ahli lintas disiplin. Namun, secara epistemik, praktik ijtihad MUI masih didominasi oleh pendekatan tekstual-normatif sehingga kurang mengintegrasikan data empiris, analisis sosial, serta pertimbangan maqâṣid secara komprehensif. Hal ini mengakibatkan fatwa-fatwa tertentu tidak sepenuhnya responsif terhadap perubahan sosial dan kebutuhan masyarakat modern. Artikel ini menyimpulkan bahwa untuk mewujudkan ijtihad yang progresif, MUI perlu memperkuat konsistensi metodologis, memperluas partisipasi ahli non-fikih, serta mengadopsi pendekatan berbasis problem solving yang sejalan dengan prinsip maqâṣid al-syarî‘ah. Temuan ini memberikan kontribusi terhadap pengembangan teori hukum Islam kontemporer, terutama dalam memahami relevansi dan tantangan ijtihad institusional di negara Muslim modern.